Reinforced Soft Soil with Pineapple Leaf Fiber - wagimin, nur amirah; A RAHMAN, NOOR KHAZANAH (Progress in Engineering Application and Technology, 2022)
Soft soil is commonly known for its low strength properties and high compressibility. This is because, the sediment process in different environmental areas as well as its physical and engineering properties of soft soil which is vacancy ratio, water content, grain size distribution, compressibility, permeability and strength show significant variations. The purpose of this study is to determine the strength improvement of the soft soil in the area of Pagoh, Johor and effectiveness of the fiber. The general properties test includes Atterberg limit test that were conducted to identify and classify the type of soil used throughout this study. Then, standard compaction and California bearing ratio test were performed to study the effectiveness of PALF on the geotechnical properties of stabilization soil. Based on the index properties results, the soil sample used in graded as medium plasticity clay soil which consisting of liquid limit (LL) more than 50% and plastic limit (PI) not more than 17%. The compaction result showed that the maximum dry density (MDD) decreases but increase at 0.50% and optimum moisture content (OMC) increase but drop at 0.50% when mixed with PALF. The result show that the CBR value significantly increases from 7.97% to 12.09% and it was achieved the highest value at 0.75% of PALF content. The finding shows that the PALF has been proven as a potential material in enhanced soil efficiency.